High prevalence of Schistosoma japonicum and Fasciola gigantica in bovines from Northern Samar, the Philippines. - Catherine A Gordon; Luz P Acosta; Geoffrey N Gobert; Mario Jiz; Remigio M Olveda; Allen G Ross; Darren J Gray; Gail M Williams; Donald Harn; Yuesheng Li; Donald P McManus (Public Library of Science (PLoS), 2015)
The cause of zoonotic schistosomiasis in the Philippines is Schistosoma japonicum, which infects up to 46 mammalian hosts, including humans and bovines. In China, water buffaloes have been identified as major reservoir hosts for schistosomiasis japonica, contributing up to 75% of human transmission. In the Philippines, water buffaloes (carabao; Bubalus bubalis carabanesis) have, historically, been considered unimportant reservoirs. We therefore revisited the possible role of bovines in schistosome transmission in the Philippines, using the recently described formalin-ethyl acetate sedimentation (FEA-SD) technique and a qPCR assay to examine fecal samples from 153 bovines (both carabao and cattle) from six barangays in Northern Samar. A high prevalence of S. japonicum was found using qPCR and FEA-SD in both cattle (87.50% and 77.08%, respectively) and carabao (80.00% and 55.24%, respectively). The average daily egg output for each bovine was calculated at 195,000. High prevalence and infection intensity of F. gigantica was also found in the bovines by qPCR and FEA-SD (95.33% and 96.00%, respectively). The identification of bovines as major reservoir hosts for S. japonicum transmission suggests that bovine treatment and/or vaccination, as one becomes available, should be included in any future control program that aims to reduce the disease burden due to schistosomiasis in the Philippines.